The relationship between dominant Western discourse and personal narratives of female genital cutting: exploring storytelling among Swedish-Somali girls and women - Palm, Camilla; Elmerstig, Eva; Holmström, Charlotta; Essén, Birgitta (Frontiers in Sociology, 2023)
A dominant narrative, that has been referred to as “the standard tale,” prevails in popular representations about female genital cutting (FGC) that often contrast with how cut women traditionally narrate their FGC experience as meaningful in contexts where FGC is customary. However, scholarship has increasingly highlighted how global eradication campaigns and migration to countries where FGC is stigmatized provides women with new frames of understandings which may lead to a reformulation of previous experiences. In this article, the storytelling itself is the subject of the analysis. Informed by focus groups (9) and individual interviews (12) with Swedish-Somali girls and women (53), the study analyzes how participants narrate and make sense of their FGC experience in a post-migration setting where FGC is stigmatized. It highlights how the participants navigate their storying in relation to “the standard tale” of FGC in their efforts to make sense of their experiences. Navigation was conducted both at an intrapersonal level through continuous identity work, yet also in relation to the social context in interpersonal encounters i.e., with service providers and others, among whom the standard tale has become a truth. Finally, the article places the analysis within broader discussions about anti-FGC work and considers the implications in relation to efforts to end FGC.